Navigating EU-Sweden forestry disputes - Richard Pokorny-Kindlman (Environmental Challenges, 2024)
This meta-empirical study delves into the conflicts between Sweden and its forestry industry in response to the EU-commission's demands for sustainable forest management. Combining theoretical foundations with empirical analysis of existing research, this study grounds itself in a clear definition of forests as intricate, adaptive, and ever-evolving systems. The central research question revolves around the efficacy of Sweden's guiding principle, ''freedom under responsibility,'' in shaping forest policy and fostering long-term sustainability.To dissect the core of this conflict, two fundamental hypotheses are explored. The first centers on the clash of interests between the Swedish government and forest industry stakeholders, while the second delves into the tension between monetarily valued ecosystem services and those without a market value, a natural market being absent. These questions are scrutinized using a novel method tailored for conflict analysis. A model article and two specific analysis articles are developed, each focusing on distinct facets of forest management, and are subsequently compared to reveal insightful contrasts.This contrasting approach unveils a comprehensive socio-economic framework underlying these conflicts—a framework that often remains concealed due to deeply ingrained patterns of thought and behavior within homogeneous groups. The method's greatest strength lies in its ability to render the invisible visible and the ''silent'' audible. It clarifies what might be obscured in the model article, bringing the contours of the conflict into sharp relief.The study findings affirm the value and democratic nature of the ''freedom under responsibility'' principle. However, for it to yield the intended outcomes, substantial and continuous educational efforts directed at relevant forest management stakeholders are imperative. This meta-empirical study highlights the necessity of a robust educational campaign to ensure the principle's success.Moreover, this study contributes theoretical insights that could serve as a foundation for conflict resolution: • Forests are complex, adaptive, and dynamic systems. • Human intervention prompts responses and adaptations within this system. • The choice of management strategies plays a pivotal role in achieving specific outcomes, whether biomass production or the preservation of natural forest characteristics. • The production of forest ecosystem services necessitates active management and does not occur automatically.